Fabrication of nickel oxide nanostructures with high surface area and application for urease-based biosensor for urea detection1. Issue 96 (17th October 2015) - Mai, Hien Duy; Sung, Gun Yong; Yoo, Hyojong
<x xml:space="preserve">Abstract</x> NiO nanostructures with high surface area were used to fabricate urease-based NiO biosensors for urea detection.